Hubungan Perilaku Bullying terhadap Interaksi Sosial Siswa SD Negeri 1 Gondang Kecamatan Gondang Kabupaten Tulungagung - Nurazizah, Galuh Ajeng; Ana, Ria Fajrin Rizqy (Universitas Nusantara PGRI Kediri, 2024)
The purpose of this research is to determine the relationship between the influence of bullying behavior on students' social interactions at SD Negeri 1 Gondang, Gondang District, Tulungagung Regency, Academic Year 2023/2024. The research method uses quantitative research methods with a correlation type. The total sample was 30 class IV and VA students at SD Negeri 1 Gondang. This research tool uses a questionnaire about bullying behavior and social interactions. The reliability value of the bullying behavior questionnaire with a reliability value of 0.749 is in the very high category, while the social interaction questionnaire with a value of 0.851 is in the very high category. The normality test using Shapiro-Wilk shows that the normality value of the bullying behavior questionnaire results is 0.976, while social interaction is 0.959, so the data is said to be normally distributed. Based on the categorization description of the two variables, bullying behavior and social interactions are in the medium category with a percentage value of 77%. The hypothesis test was analyzed using product moment correlation, which explains that the correlation between bullying behavior and students' social interactions was 0.533 with a significance value of 0.002. The value is 0.400-0.599, which means it is quite strong, with a positive relationship direction so that the lower the bullying behavior, the higher the social interaction.